IMPLEMENTATION OF CHARACTER-BASED STUDENT EXTRACURRICULARS IN SD NENDER 9 MENDO BARAT - muhammad iqbal arrosyad; Chairul Fuad; Sefty Amelya; Hayuna Hayuna; Susni Martuti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This study aims to determine the extracurricular activities that are found in SD Negeri 9 Mendo Barat in shaping the character and interests of students.. This research method uses descriptive-qualitative, data collection used are interviews, observation, documentation, and sources analyzed using inductive data analysis techniques. The results showed that extracurricular activities made a positive contribution to the formation of character in students' discipline in SD Negeri 9 Mendo Barat. High school students following extracurricular activities at school have better discipline and shape the personal character of students more than other students. Attitudes in the form of discipline, following the flag ceremony, coming on time, neatly dressed according to school rules, obeying the teacher, keeping clean, not playing truant, not getting involved in a fight, not smoking, respecting the elders not making a fuss during learning or hours take a break, obey the schedule of school activities. extracurricular which is much in the interest of scouts